 ## Blog

### The Quest for 700: Weekly GMAT Challenge (Answer)

Yesterday, Manhattan GMAT posted a GMAT question on our blog. Today, they have followed up with the answer:

One first natural move is to factor 52 out of the numeric expression:

52 + 54 + 56 = 52(1 + 52 + 54)

Meanwhile, (a + b)(ab) becomes a2b2.

So, somehow we have to turn 52(1 + 52 + 54) into a difference of squares. It must come down to the stuff in the parentheses.

Flip around those terms, so that we have the larger powers first: 54 + 52 + 1.

This should look almost like a special product: (x + y)2 = x2 + 2xy + y2, if x = 52 and y = 1. In fact, write that out:
(52 + 1)2 = 54 + 2(52) + 1

The expression we actually have, 54 + 52 + 1, is very close. Add 52 and subtract it as well:

54 + 52 + 1
= 54 + 52 + 1 + 52 – 52
= (54 + 52 + 1 + 52) – 52
= (54 + 2(52) + 1) – 52
= (52 + 1)2 – 52
= 262 – 52

Almost there. Remember, we had 52 as well:

52 + 54 + 56 = 52(1 + 52 + 54) = 52(262 – 52)
= (26×5)2 – (5×5)2
= 1302 – 252.

Other differences of squares can be equal to the original expression, but this is the only one that fits an answer choice: (E) 25.

There are other ways to solve this problem as well, such as backsolving.
52 + 54 + 56> = a2b2
52 + 54 + 56 + b2>= a2

Try different b’s from the answer choices, and see which one, when added to the original expression, gives you a perfect square.

Testing (E):
52 + 54 + 56 + 252
= 52 + 54 + 56 + 54
= 52 + 2×54 + 56
= (5 + 53)2
This is the only answer that fits.

#### Upcoming Events

• Dartmouth Tuck (Round 2)
• Michigan Ross (Round 2)
• Virginia Darden (Round 2)
• Cornell Johnson (Round 2)
• Harvard (Round 2)
• London Business School (Round 2)
• Penn Wharton (Round 2)
• Texas McCombs (Round 2)
• UNC Kenan-Flagler (Round 2)
• USC Marshall (Round 2)